Leisure, sedentary lifestyle and health in Ecuadorian teenagers - Chávez Cevallos, Enrique; Sandoval Jaramillo, María Lorena (Revista Cubana de Medicina General Integral, 2016)
Introduction: The study of leisure not only favors an approach to the time dedicated to non-working activities, but also to relate recreational habits with levels associated to physical inactivity and health. Objective: This research paper focuses on the evaluation of leisure (active and passive) of Ecuadorian adolescents and their relationship with the existing level of physical inactivity. Methods: To this end, the Ecuadorian reality was adapted into a survey of Leisure, similar to the ages studied, applied in countries like Colombia, Cuba, Chile, Paraguay and Uruguay; and PAQ-A (Physical Activity Questionnaire for Adolescents) internationally used and validated. It was taken a sample of 429 students aged 12-13 years, 438 (14-15 years) and 430 (16-17 years), obtaining a sample size of 1 297 students from Colegio Nacional Juan de Salinas. Results: The results show that in their leisure students dedicate 47.16% to passive activities with a predominant use of technology, listen to music and watch TV; 19,91% to dynamic activities with a predominance of walking, going to the disco and sports. Conclusion: It is shown that the misuse of leisure is favouring a marked physical inactivity in adolescents, laying the foundation for the subsequent design of a program of physical and recreational activities according to the socio-economic, historical and cultural conditions of the Ecuadorian mountain range.